An educational programme to facilitate reflective practice of registered nurses in training hospitals in Windhoek - Nelumbu, L. N.; Dyk, A. van (International Journal of Advanced Nursing Studies, 2014)
Problems or incidents occurring in clinical settings are often seen as indicators of poor nursing care and even indicators of a lack of reflective practice skills. In the hope of improving such situations a qualitative, explorative, phenomenological, descriptive and contextual approach was conducted to explore and describe how reflective practice is practised by registered nurses in training hospitals in Windhoek. The findings of this study revealed inadequate knowledge of reflective practice among registered nurses. This paper represents the findings of situational analysis of the experiences of registered nurses on reflective practice. Keywords: Facilitate, Reflection, Reflection-In-Action, Reflection-on-Action, Reflective Practice.